Epigenetic Carcinogenesis and Malignancy: The Significance of Migratory Potential (Journal of Cancer Research Updates, 2023)
The essential feature of the malignant phenotype is the ability of the affected cells to transgress the normal territorial limits that delineate tissue boundaries. This brief review outlines the process underlying the acquisition of this property based on evidence consistent with the notion that the mechanism of carcinogenesis involves defective epigenetic transmission. The resulting failure of vertical transmission of the differentiated pattern of gene expression in proliferative stem cells which leads to faulty copying of the epigenetic information at each cell division generates widespread genetic abnormalities; a process which is essentially equivalent to a greatly elevated mutation rate. The outcome from the point of view of the affected cell and its progeny would be expected to interfere negatively with the proliferation rate. To some extent this proliferative disadvantage is offset by the altruistic factor necessary for permitting coexistence of different cell types in multicellular organisms but the crucial property which renders certain cells malignant is their ability to transgress tissue boundaries. Affected cells possessing this malignant phenotype are able to penetrate this barrier and enter microenvironmental zones where they are able to proliferate without competition. The competitive growth process is outlined using a simple microenvironmental model.